Estudio etnográfico de la situación actual de los afroecuatorianos: sus prácticas culturales e imaginarios sociales - Proaño Revelo, Jessica Paola (2015)
In this study we seek to describe Ethnographic cultural events and social practices of a Pueblo del Valle of Chota, Piquiucho, collecting basic information about their origins and development of life in time. Through the study done, we also made a diagnosis of spatiality, their location, their ways of life in this space, as well as the conditions currently live. In the interviews we had with members of the community, we made a comparative analysis with reality and the transformation that occurred since the arrival of the first African descent in Ecuador, the life experiences that were reported were the mainstay, to meet as was the life of the oldest and most representative members of the community, data are collected in the first chapter. When the second chapter the main findings we found, data relate to the material conditions of the community, housing, education and health infrastructure situation. We did a theory in order to understand their culture universe approaches. Through field exploration, we could identify the traditions of the inhabitants, we attended celebrations, and we demonstrate the importance and meaning in their daily lives. The fourth chapter is a communicative product with photos and interviews with their characters, reflects the space where they live and their stories, contains the voice of the elders of the village headman Piquiucho d, and a native academic community, which complement the study.